A Field on Fire : The Future of Environmental History - Steinberg, Theodore, 1961-; Hersey, Mark D. (Book collections on Project MUSE., 2019)
"The eighteen essays in "A Field on Fire" present new research paths in topics that are especially promising but insufficiently developed or altogether neglected in the field of environmental history"--